3D printable carboxylated cellulose nanocrystal-reinforced hydrogel inks for tissue engineering. (13th March 2020) - Kumar, Anuj; I Matari, Ibrahim Abdullah; Han, Sung Soo
Abstract: To achieve a three-dimensional (3D) microenvironment for complex tissue regeneration is a great challenge when developing biomaterials as artificial extracellular matrix (ECM) with properties similar to that of native tissue. Polysaccharide-based hydrogel shows great potential as ECM in the regeneration of damaged tissues or reconstruction of organs, demonstrating properties similar to those of native ECM. Extrusion 3D printing of cell-free or cell-loaded hydrogel ink has led to a more sophisticated fabrication of the desired compositions and architectures for tissue engineering applications. The development of stable cell-free and cell-loaded hydrogel inks with optimal physicochemical properties and biocompatibility is also a major concern in direct-write extrusion-based 3D printing. In this study, carboxylated cellulose nanocrystals (cCNCs) were prepared using ammonium persulfate, where transmission electron microscopy, Fourier-transform infrared spectroscopy, and x-ray diffraction analyses confirmed their successful preparation. Further, the effect of cCNCs (–COOH) and/or xanthan gum (XG) (–COOH) was evaluated on the rheological behavior of the sodium alginate (SA) hydrogel matrix. The incorporation of cCNCs and XG manipulated the flow and shear-thinning behavior of the hydrogel inks, thereby improving the printing ability. The results showed good rheological properties, post-printing fidelity, and dynamic mechanical properties under compression of the developed hydrogel inks. Furthermore, good viability of the human skin fibroblast (CCD-986Sk) cells on bulk hydrogels (hydrogel inks) was observed, as demonstrated by both qualitative and quantitative cell analyses. The use of cCNCs and XG in SA hydrogel inks provides a primary insight for further improvement in designing 3D bioprintable hydrogel inks.